Green synthesis and characterization of gold nanoparticles from Pholiota adiposa and their anticancer effects on hepatic carcinoma - Zhongwei Yang; Zijing Liu; Junmo Zhu; Jie Xu; Youwei Pu; Yixi Bao (Taylor & Francis Group, 2022)
Gold nanoparticles (AuNPs) were successfully fabricated by Pholiota adiposa polysaccharide (PAP-1a) without employing any other chemicals. The physical and chemical properties of PAP-AuNPs were determined using transmission electron microscopy (TEM), dynamic light scattering (DLS), energy-dispersive X-ray spectroscopy (EDXR), Fourier-transform infrared spectroscopy (FT-IR), and atomic force microscopy (AFM). In an attempt to analyze the immune regulation, antitumor effect, and biological safety, the production of NO and TNF-α, IL-12p70, and IL-1β from RAW264.7 as well as the proliferation of RAW264.7 were detected in vitro. Flow cytometry was conducted to determine the ratio of the CD4+/CD8+ cell in peripheral blood and immunohistochemical analysis involving hematoxylin and eosin (H&E) and proliferating cell nuclear antigen (PCNA) staining were conducted in vivo. The results of this study showed that PAP-AuNPs had a significantly improved immune regulation and anti-tumor effect in comparison to PAP-1a alone. PAP-AuNPs showed no toxicity both in vivo and in vitro. This study demonstrates a useful application of PAP-AuNPs as a novel nanomedicine for hepatic carcinoma.